Prototipe Smart Mosque System Untuk Persiapan Sarana Sebelum Waktu Shalat Berbasis IoT - Kafrawi, Achmad Evin; Ch, Syafaruddin; Kanata, Bulkis (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The advancement of technology in the modern era has driven the development of innovations that facilitate human activities, one of which is through the concept of the Internet of Things (IoT). This research aims to develop a smart mosque prototype based on IoT to prepare facilities before prayer times. The issue faced by several mosques is the lack of a permanent caretaker, which often leads to delays in preparing for worship, such as filling the ablution water or playing the Quran recitation before the call to prayer, as well as the management of facilities like lighting and fans that are not well controlled. The proposed solution in this research utilizes the NodeMCU ESP32 microcontroller, an ultrasonic sensor to detect the water tank capacity to ensure water is available, a DFPlayer Mini to automatically play the Quran recitation before the call to prayer, the MyQur’an API to retrieve prayer times, and the NTP (Network Time Protocol) server to synchronize the system time accurately. Additionally, the Blynk application is used to control the facilities within the mosque. Based on the test results, this prototype system demonstrates good performance in controlling mosque facilities, automatic water filling, and timely Quran recitation playback. However, in the automatic water filling, there is a limitation regarding the high filling threshold, where water overflows at 90% and 95% levels. The DS1307 RTC system has also proven capable of synchronizing time accurately with the prayer schedule from the MyQur’an API, with minimal time difference.